Cellulose Electro-Active Paper: From Discovery to Technology Applications - Abas, Zafar; Kim, Heung Soo; Kim, Jaehwan; Kim, Joo-Hyung (Frontiers in Materials, 2014)
Cellulose electro-active paper (EAPap) is an attractive material of electro-active polymers (EAPs) family due to its smart characteristics. EAPap is thin cellulose film coated with metal electrodes on both sides. Its large displacement output, low actuation voltage and low power consumption can be used for biomimetic sensors/actuators and electromechanical system. Because cellulose EAPap is ultra-lightweight, easy to manufacture, inexpensive, biocompatible, and biodegradable, it has been employed for many applications such as bending actuator, vibration sensor, artificial muscle, flexible speaker, and can be advantageous in areas such as micro-insect robots, micro-flying objects, microelectromechanical systems, biosensors, and flexible displays.